Synergising mixture DoE with CFD for ash-slurry optimisation. (2016) - Malik, Subhash; Singh, Bikram Jit
Present research work describes the issues associated with slurry transportation systems in thermal power plants. It not only explores the importance of such ash handling systems but also embarks upon a step-by-step procedure to optimise slurry contents, without ignoring flow process parameters like velocity and pipe diameter to ensure least possible drop in the flow pressure, along the length of pipe. After analysing the research gaps, a strategic methodology based on the philosophies of mixture design of experiments (DoE) and computational flow dynamics (CFD) was suggested. Experiments were designed and performed in a balanced orthogonal matrix, before simulating through CFD. A deviation of mere 8% (approximately) was found in the end results, and hence an average drop in pressure from 3176 to 1252 KPa was unleashed, in the first attempt itself. The rheological properties (like pH value or settling properties) of slurry were assumed to be in required ranges and their relative impacts on critical flow metrics of slurry transportation system were not studied. The present study used an integrated approach to study the flow and further proved its authenticity by implementing it in an Indian thermal power plant successfully.